Paus Fransiskus dan Kepemimpinan Perempuan dalam Gereja Katolik - Monteiro, Yohanes Hans; Widyawati, Fransiska (Faculty of Theology Duta Wacana Christian University, 2024)
AbstractThe position and leadership of women in the Catholic Church has been a long debate. The church is considered patriarchal because it still marginalizes women in ordination which allows women to become leaders in this institution. This article critically examines how the Church, especially Pope Francis, provides a place for women’s leadership in the Catholic Church. This research employs literature study or library research as its method. This study found that in the 10 years of his leadership, Pope Francis has provided open space for women in various aspects of Church leadership. He placed women in positions previously only given to men and clergy. However, in the aspect of ordination, Pope Francis still continues and upholds the old tradition of special ordination only for men. Regarding this, there are camps that are pro and there are those who are against. For those who are against it, Pope Francis and the Catholic Church are still considered to be gender biased in aspects of leadership. AbstrakPosisi dan kepemimpinan perempuan di dalam Gereja Katolik telah menjadi perdebatan yang panjang. Gereja dianggap patriarkat karena masih memarginalkan perempuan dalam tahbisan yang memungkinkan perempuan menjadi pemimpin di dalam institusi ini. Artikel ini secara kritis mengkaji bagaimana posisi Gereja Katolik, khususnya Paus Fransiskus dalam memandang kepemimpinan dan tahbisan perempuan di dalam Gereja Katolik. Metode penelitian yang dipakai adalah studi pustaka. Penelitian ini menemukan bahwa dalam 10 tahun kepemimpinannya Paus Fransiskus telah memberi ruang bagi perempuan dalam aneka aspek kepemimpinan Gereja. Ia menempatkan perempuan pada posisi yang sebelumnya hanya diberikan kepada laki-laki dan klerus. Namun, dalam aspek tahbisan, Paus Fransiskus masih melanjutkan dan menjunjung tradisi lama penahbisan khusus hanya bagi laki-laki. Terhadap hal ini, ada kubu yang pro dan ada yang kontra. Bagi yang kontra, Paus Fransiskus dan Gereja Katolik dianggap masih bias gender dalam aspek kepemimpinan.